MISS HAVISHAM’S ROLE TOWARDS ESTELLA’S PERSONALITY AS SEEN IN GREAT EXPECTATION BY CHARLES DICKENS - RISMA KARTIKA DEWI; DWI RETNO NOVEMI MAULIDIYAH (Fakultas Sastra Universitas Gresik, 2018)
This study is conducted to get better understanding regarding the role of family, particularly the role of mother towards personality of the child. In holding her role as an adopted mother for Estella, Miss Havisham adopts the type of parenting style in which she fully dominates and eleminates the rights of Estella. Miss Havisham has an intention to do the twisted revenge on men. She uses Estella as her media of taking revenge. She puts her ambition on Estella without considering Estella’s desire. Her own disappointment leading her to foster an adoptive daughter under her control. The writer interests to discuss more detail whether Miss Havisham’s parenting style can influence to the personality of Estella or not. In Writing the thesis, the writer uses literary approach which is linked with descriptive qualitative. After collecting the data, the writer classifies and clarifies the data which are related to the topic being discussed. The finding of this study shows that there is parent involvement process in forming Estella’s thought, identity and achievement. The writer concludes that Miss Havisham’s parenting style is not the best way in parent involvement process because it generates the negative impacts on Estella’s personality. Key words : Role, Parenting Style, and Motive